2015
DOI: 10.5455/ijmsph.2015.0809201423
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal sonography in early management of subclinical varicocele and male infertility

Abstract: Background: Varicocele is the most common cause of male infertility. About 20-30% men with varicocele are infertile. The clinically obvious varicocele is identifiable and correctable cause of male infertility, but less is known about the subclinical varicocele and its relationship to infertility. However, subclinical varicocele seems to be an important cause of infertility and hence scrotal ultrasonography is increasingly used in the diagnosis of subclinical varicocele. This study was undertaken to reveal inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Prajapati, Jadeja, and Patel () reported that scrotal CDU might be an important technique for detecting SV, as well as for the early diagnosis and management of male infertility. Their study used the CDU and WHO guidelines () for diagnosing SV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prajapati, Jadeja, and Patel () reported that scrotal CDU might be an important technique for detecting SV, as well as for the early diagnosis and management of male infertility. Their study used the CDU and WHO guidelines () for diagnosing SV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Prajapati et al. () reported no significant difference in testicular volume in infertile patients with SV, but whether subfertile patients with SV had smaller testis remained under debate. The present study is the first to demonstrated that SV patients with PRF >29 cm/s and total testicular volume <27 cc have higher chances of male subfertility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been validated to be secondary to assorted abuses, which include high scrotal temperature with loss of scrotal counter-cooling mechanism, gonadotropins or autoimmunity, oxidative stress, and reflux of adrenal metabolites. 2 Semen parameters are reported to be enhanced by varicocelectomy in almost 70% of the infertile male population as well as 40% of the population will accomplish pregnancy consequently. It is postulated that Sertoli cell dysfunction and low testosterone might be intertwined concerning the influence of testosterone on spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, testosterone is produced in the testis. 2 The alteration of spermatogenesis is associated with an increase in serum FSH and a decrease in testosterone levels. Different categories of sperm concentration in infertile men have been revealed from the FSH concentration, which includes oligozoospermia and azoospermia.…”
Section: Introductionmentioning
confidence: 99%